2021
DOI: 10.3389/fphys.2021.680005
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Sirtuins and Klotho in Cardioprotective Effects of Exercise Training Against Waterpipe Tobacco Smoking-Induced Heart Dysfunction

Abstract: Despite its negative effect on the cardiovascular system, waterpipe smoking (WPS) is currently popular worldwide, especially among youth. This study investigated the effects of moderate endurance exercise on heart function of rats exposed to WPS and its possible mechanism. The animals were randomly divided into four groups: control group (CTL), the exercise group (Ex) which trained for 8 weeks, the waterpipe tobacco smoking group (S) exposed to smoke inhalation (30 min per day, 5 days each week, for 8 weeks), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Studies in elderly participants revealed that resistance PE training increases serum levels of SIRT1, SIRT3, SIRT5, and SIRT6 proteins after 12-weeks interventions (Hooshmand-Moghadam et al, 2020;Wasserfurth et al, 2021). Similarly, increased levels of SIRT3 and SIRT4 have been reported in many studies involving rats that underwent short-term (Lensu et al, 2019;Alavi et al, 2021;Heiat et al, 2021) and long-term PE (Nogueira-Ferreira et al, 2019). In sum, it seems clear that sirtuin regulation acts as one of the key mechanisms by which PE can improve cognitive functions, under both normal and pathological conditions.…”
Section: Sirtuins and Physical Exercisementioning
confidence: 69%
“…Studies in elderly participants revealed that resistance PE training increases serum levels of SIRT1, SIRT3, SIRT5, and SIRT6 proteins after 12-weeks interventions (Hooshmand-Moghadam et al, 2020;Wasserfurth et al, 2021). Similarly, increased levels of SIRT3 and SIRT4 have been reported in many studies involving rats that underwent short-term (Lensu et al, 2019;Alavi et al, 2021;Heiat et al, 2021) and long-term PE (Nogueira-Ferreira et al, 2019). In sum, it seems clear that sirtuin regulation acts as one of the key mechanisms by which PE can improve cognitive functions, under both normal and pathological conditions.…”
Section: Sirtuins and Physical Exercisementioning
confidence: 69%
“…SIRT1 can also decrease the inflammation, modulating the redox-sensitive nuclear factor kappa B (NF- κ B), and enhance the expression of the antioxidant enzymes Catalase and Superoxide dismutase 77 , 78 . Exercise training increased the levels of SIRT1, SIRT3 and the anti-apoptotic Bcl-2 in the heart, while the level of the proapoptotic protein Bax decreased 79 . Moreover, exercise training in humans can act on the body increasing the DNA repair capacity and antioxidant responses 26 .…”
Section: Discussionmentioning
confidence: 92%
“…The tobacco smoke was blown into the chamber for 30 s, then the smoke valve was closed, and the fresh air inlet was opened for 30 s to clear the chamber. Finally, the animals were allowed to inhale fresh air for another 30 s. This cycle was repeated 20 times daily for a total of 30 min per day for 5 days a week for the WTS subgroups during the indicated period ( 22 24 ). During smoking, the level of CO concentration was maintained at 907 ± 108 ppm in the chamber using a Testo 310 measurement device (Testo Ltd., Lenzkirch, Germany) ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…The stimulation of angiogenesis is one of the mechanisms of bone repair by PTH where, for example, PTH stimulates VEGF secretion in osteoblasts ( 21 , 22 ). Furthermore, PTH secretion has been shown to be significantly lower in smokers than in non-smokers independently of vitamin D and calcium levels ( 24 ).…”
Section: Introductionmentioning
confidence: 99%